Impact of extra-articular spondyloarthritis manifestations and comorbidities on drug retention of a first TNF-inhibitor in ankylosing spondylitis: a population-based nationwide study. Issue 2 (15th October 2018) - Lindström, Ulf; Olofsson, Tor; Wedrén, Sara; Qirjazo, Ilia; Askling, Johan
Abstract : Objectives: To assess the impact of extra-articular spondyloarthritis (SpA) manifestations (anterior uveitis, psoriasis and inflammatory bowel disease (IBD)), and of comorbidities, on tumour necrosis factor alpha inhibitor (TNFi) drug retention in ankylosing spondylitis (AS). Methods: We identified all bio-naïve patients with AS starting a first ever TNFi July 2006 to December 2015 from the Swedish Rheumatology Quality register and followed these from treatment start through December 2015. We determined the presence of extra-articular SpA-manifestations, comorbidities (cardiovascular disease, affective disease, diabetes, malignancies, chronic lung disease and kidney disease) and socioeconomic status before TNFi start, through linkage to five other national registers, and calculated, for each factor, crude and adjusted HRs for discontinuing the TNFi. Results: 2577 patients with AS (71% men) started a first TNFi during the study period. 27% had a history of anterior uveitis, 6% psoriasis and 7% IBD. Anterior uveitis was associated with a superior TNFi drug retention (HR 0.72; 0.62 to 0.83), psoriasis with an inferior (HR 1.48; 1.18 to 1.86), whereas IBD did not affect TNFi drug retention. The effect of the SpA manifestations on TNFi drug retention was of a similar magnitude to that of the comorbidities. Conclusions: In AS, anterior uveitis and psoriasis, but not IBD, affect TNFi drug retention. Possible explanations include differential effects of TNFi on these extra-articular SpA manifestations, or inherent differences in AS, associated with the inflammatory phenotype. Further, comorbidities and socioeconomy affect TNFi drug retention to a similar magnitude as the SpA manifestations, and should, as such, receive due attention in clinical practice.